2017
DOI: 10.1002/rcm.8008
|View full text |Cite
|
Sign up to set email alerts
|

Precise carbon isotopic ratio analyses of micro amounts of carbonate and non‐carbonate in basalt using continuous‐flow isotope ratio mass spectrometry

Abstract: The measured δ C values decrease substantially at lower carbon concentration and higher sample weights, and poorer precision is obtained. Suggestions are made to measure repeatedly the same carbon concentration of sample and reference materials in order to obtain not only reproducible, but also accurate carbon isotope ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Considering the need for high‐precision δ 13 C analysis to normalize small samples, such as in the analysis of foraminifera 39,40 and basalt, 41 carbonate RMs must be well homogenized 30 . Several studies have demonstrated that using an isotope‐ratio mass spectrometer with a GasBench can achieve high‐precision δ 13 C analyses, 38,40–45 and methods for analyzing microgram masses of carbonate have been in use for decades 38,41,43 . For this reason, we carried out homogeneity tests with a GasBench as specified above at the RSIL and a MultiCarb system at Geotop.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the need for high‐precision δ 13 C analysis to normalize small samples, such as in the analysis of foraminifera 39,40 and basalt, 41 carbonate RMs must be well homogenized 30 . Several studies have demonstrated that using an isotope‐ratio mass spectrometer with a GasBench can achieve high‐precision δ 13 C analyses, 38,40–45 and methods for analyzing microgram masses of carbonate have been in use for decades 38,41,43 . For this reason, we carried out homogeneity tests with a GasBench as specified above at the RSIL and a MultiCarb system at Geotop.…”
Section: Resultsmentioning
confidence: 99%
“…The overall standard deviation of 0.07 mUr from the nine bottles with 26 analyses at 0.10-mg of USGS44 is slightly higher than 0.05 mUr from 0.70-mg analyses of USGS44, and this is thought to be caused by a variable carbon blank from the tin capsules. The average δ 13 C value of −40.08 mUr from USGS44 in Table 3 is the result of singlepoint normalization against NBS 19. Considering the need for high-precision δ 13 C analysis to normalize small samples, such as in the analysis of foraminifera 39,40 and basalt, 41 carbonate RMs must be well homogenized. 30 Several studies have demonstrated that using an isotope-ratio mass spectrometer with a GasBench can achieve high-precision δ 13 C analyses, 38,[40][41][42][43][44][45] and methods for analyzing microgram masses of carbonate have been in use for decades.…”
Section: Online Combustion Continuous-flow Irmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The repeatability of the total analytical procedure is in the range of 0.1−0.2‰. The experiments are conducted following the analytical method described in Zha et al 51 The δ 13 C VPDB values of coal samples are presented in Table 1.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%